Sumatran Pale Hedge Blue Udara dilecta neodilecta (Corbet, 1937) (Lepidoptera: Lycaenidae) in Kerinci Highlands, a southernmost record - Muhammad Iqbal; Arum Setiawan; Indra Yustian (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2020)
Two tiny individuals of Sumatra Pale Hedge Blue Udara dilecta neodilecta (Fruhstorfer, 1910) were observed and documented on 18 August 2014 in Lake Kaco of Kerinci Highlands, Jambi Province. This butterfly was determined using appropriate guides. Finding of Udara d. neodilecta represent a southernmost recordÂ  (020S) for this Sumatran endemic subspecies in its range.